2021
DOI: 10.1371/journal.pone.0251796
|View full text |Cite
|
Sign up to set email alerts
|

MADRID+90 study on factors associated with longevity: Study design and preliminary data

Abstract: The progressive aging of the population represents a challenge for society. In particular, a strong increase in the number of people over 90 is expected in the next two decades. As this phenomenon will lead to an increase in illness and age-related dependency, the study of long-lived people represents an opportunity to explore which lifestyle factors are associated with healthy aging and which with the emergence of age-related diseases, especially Alzheimer’s type dementia. The project “Factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…Studies from several countries have shown the importance of adopting healthy lifestyles, throughout life, aiming at a healthy aging process [7][8][9] . Studies in France 10 and in the United RESUMO: Objetivo: Estimar as prevalências dos comportamentos saudáveis entre os indivíduos de 30 anos ou mais com diagnóstico de hipertensão arterial e diabetes mellitus utilizando as informações da Pesquisa Nacional de Saúde, 2019.…”
Section: Introductionunclassified
“…Studies from several countries have shown the importance of adopting healthy lifestyles, throughout life, aiming at a healthy aging process [7][8][9] . Studies in France 10 and in the United RESUMO: Objetivo: Estimar as prevalências dos comportamentos saudáveis entre os indivíduos de 30 anos ou mais com diagnóstico de hipertensão arterial e diabetes mellitus utilizando as informações da Pesquisa Nacional de Saúde, 2019.…”
Section: Introductionunclassified
“…The number of patients over 85 years of age undergoing PPV surgery has increased significantly and is expected to continue to increase in the future, due to the longer life expectancy. Some regions, such as Madrid, have particularly high life expectancy, highlighting the importance of population ageing [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%